Understanding Youngsters’ Buying Behavior in E-Retail : A Conceptual Framework - Singh, Archana; Panackal, Nehajoan; Bommireddipalli, Ravi Teja; Sharma, Adya (Indian Journal of Marketing, 2016)
Purpose : India being the youngest country in the world, youngsters comprise of a significant share of sales for marketers. Youngsters are tech savvy and are the radar of every marketer in India. The purpose of this paper was to understand the influence of digital media on youngsters' buying behavior in retail. To address this gap, this paper developed a theoretical framework and the factors identified are grounded in literature review. Design/Methodology/Approach : To the researchers, this study highlights the important variables which have been arrived at on the basis of systematic literature review. The factors were listed through literature review and then, a qualitative and interpretive tool, ISM was applied. Originality : Our study is unique and innovative as we have focused on exploring the different effects of the relationship youngsters have with buying behavior and e - retail. The framework proposed in this paper can be utilized to develop marketing strategies to target young consumers. In the Indian context, this is a good study done for targeting Indian youth by Indian marketers in the retail sector. Findings : The youth quotient and digital media emerged as the most important factor, followed by consumerism. Interrelations otherwise not easily observable established their prominence. An important fact that evolved is that almost all the factors had interdependence and were in coherence. Limitations : The research limits itself to a conceptual understanding of buying behavior amongst youngsters for online shopping; however, it does not show the results at a microscopic level. It is inclusive of factors at the macro level. The outcome is based on intense literature review. Directions for Further Research : The present study needs to be further investigated under the light of market dimensions and issues. The model developed can be empirically validated by utilizing the conceptual framework.